Prevalence and Risk Factors of Polycystic Ovary Syndrome (PCOS) Among Adolescent Girls in Urban and Rural Pakistan - Aslam, Maham; Iqbal, Hira; Jabeen, Shumaila (Biological and Clinical Sciences Research Journal, 2025)
Polycystic Ovary Syndrome (PCOS) is a common endocrine disorder affecting females during adolescence and reproductive years, with increasing prevalence in South Asia. This study aimed to determine the prevalence of PCOS and identify associated clinical and lifestyle risk factors among adolescent girls in urban and rural areas of Pakistan. Methods: A cross-sectional study was conducted at Jamila Fareedi Medical Center in Pakistan from April to September 2024. Eighty-six adolescent girls aged 13–19 were recruited from urban and rural settings. PCOS was diagnosed based on the Rotterdam criteria. Clinical assessments included anthropometric measurements, menstrual history, signs of hyperandrogenism, and lifestyle factors. Biochemical investigations included levels of LH, FSH, testosterone, and insulin. Insulin resistance was calculated using HOMA-IR. Data were analyzed using SPSS v26, with p < 0.05 considered statistically significant. Results: The overall prevalence of PCOS was 26.7%, with a higher prevalence among urban girls (34.1%) compared to rural girls (19.0%). PCOS was significantly associated with a higher BMI (p = 0.02), physical inactivity (p = 0.01), frequent consumption of junk food (p = 0.006), sleep deprivation (p = 0.01), and an elevated LH: FSH ratio (p < 0.001). Hirsutism, acne, and menstrual irregularities were more prevalent in the PCOS group. Insulin resistance (HOMA-IR > 2.5) was observed in 60.9% of patients with PCOS compared to 17.5% of non-PCOS participants. Conclusion: PCOS is prevalent among adolescent girls in Pakistan, particularly in urban areas, and is strongly associated with modifiable lifestyle and metabolic risk factors. Early screening, education, and targeted interventions are urgently needed to prevent long-term reproductive and metabolic complications.